Soil heterotrophic respiration repressed by drought stress more than soil autotrophic respiration in Stipa breviflora desert steppe, China - Chunxue Han; Zhiqiang Sun; Haigang Li (Scientific Reports)
Abstract Quantification of soil carbon emissions in desert steppes is a key issue in determining the carbon budget in arid regions. However, the changes in and driving mechanisms of soil respiration and its components in response to drought in ecosystems under long-term water stress remain unclear. In this study, rain reduction by 30% and 50% experiments were conducted to simulate drought during the growing season in 2023 in the Stipa breviflora desert steppe. Total soil respiration and soil heterotrophic respiration were measured, and simultaneously, the surface soil temperature and moisture were measured at 0–10 cm. Surface soil microorganisms, microbial biomass carbon, and enzymatic activity were also tested. The results showed that drought significantly decreased soil microbial biomass carbon and enzymatic activity, but had no significant effects on soil microbial richness and diversity, as well as the dominant flora. The inhibitory effect of drought on soil autotrophic respiration only appeared at the beginning of the growing season and then disappeared with plant growth because of the drought-resistant ability of perennial plants in the desert steppe. Heterotrophic respiration is the primary soil carbon release process occurring in the desert steppe, approximately four times that of autotrophic respiration. Soil temperature and moisture jointly regulated heterotrophic respiration under extreme drought conditions (rainfall reduction of 50%); however, their influence on autotrophic respiration became insignificant. This study indicates that drought slowed the decomposition of soil organic carbon and had a weak effect on plant root respiration in the S. breviflora desert steppe. The response process of Rs and its components to drought stress provided theoretical basis for soil carbon feedback in desert steppe under extreme drought conditions.